Tapioca starch-based films containing oregano, Vietnamese mint, and curry leaf essential oils for food packaging applications - Othman, Siti Hajar; Kahar, Nurul Syafqah; Nordin, Norhazirah; Alyas, Nur Diyana; Noor Hasnan, Noor Zafira; Abdul Talib, Rosnita; Karyadi, Joko Nugroho Wahyu (Universiti Putra Malaysia, 2023)
Sustainable food packaging made from starch is a viable alternative to the usage of petrochemical-based plastics. The incorporation of additives, particularly essential oils, into the starch film can potentially improve the mechanical properties and enhance its functionality. The present work investigated the effects of the incorporation of different types and concentrations (0, 0.25, 0.5, 0.75, and 1%; v/v) of essential oils (EOs) from oregano, Vietnamese mint (VEO), and curry leaf on the mechanical and optical properties of starch films. Additionally, the quality attributes of strawberries wrapped using the films during storage were investigated in terms of weight loss, colour changes, and firmness. It was observed that the incorporation of EOs into the starch films improved the elongation at break, especially at higher concentrations. These films became slightly yellowish and more opaque. Besides, the changes in quality attributes of strawberries wrapped with starch/EOs films were the lowest as compared to the unwrapped strawberries and the strawberries wrapped with starch films. Starch films incorporated with 1% (v/v) VEO were the most effective films due to relatively high flexibility and low stiffness, apart from the ability to decrease the changes in quality attributes of strawberries. To conclude, the starch/EOs films have great potential for food packaging applications.